Pengaruh Kualitas Pelayanan Dan Store Atmosphere Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada CV. Istana Mobil - Sabilla, Ella; Siahaan, Rumiris; Cen, Cia Cai (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2023)
This study aims to determine the effect of service quality and store atmosphere on customer loyalty with satisfaction as an intervening variable at CV. Istana Mobil. The research method used is a quantitative method using the help of SPSS version 25.00. which is collected from the results of distributing questionnaires to CV customers. CV. Istana Mobil Tebing Tinggi City as many as 96 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination (R2) analysis, hypothesis testing, namely T test and path analysis. The results of SPSS in this study are the Service Quality variable (X1) has an effect on the Customer Satisfaction variable (Z), the Store Atmosphere variable (X2) has no effect on the Customer Satisfaction variable (Z), the Service Quality variable (X1) has no effect on Customer Loyalty variable (Y), the Store Atmosphere variable (X2) has no effect on Customer Loyalty variable (Y), the Customer Satisfaction variable (Z) has an effect on Customer Loyalty variable (Y) and path analysis shows that Customer Satisfaction variable (Z) can mediate the relationship between Service Quality variable (X1) and Customer Loyalty variable (Y), and Customer Satisfaction variable (Z) can mediate the relationship of Store Atmosphere variable (X2) to Customer Loyalty variable (Y).